Perkawinan dalam Islam di Era Modern: Tinjauan Perspektif Siti Musdah Mulia - Zahratus Syaidah Nasution; Azizah Azizah; Nabila Rizky; Selpiani Selpiani; Naila Mumtazah; Alif Eko Putro Santoso (STIKes Ibnu Sina Ajibarang, 2025)
This article discusses Siti Musdah Mulia's views on marriage in Islam, with a focus on the definition of marriage, the practice of polygamy, marriage registration, and the ideal age for marriage. As an academic and activist, Musdah Mulia proposed the concept of marriage as an equal contract between two individuals, and emphasized the importance of registering marriages to protect women's rights. He criticized polygamy and encouraged monogamy as a marriage model that is more in line with the principles of justice and gender equality. Apart from that, Musdah Mulia proposes a minimum age of 20 years for marriage, considering aspects of physical and psychological maturity. This article uses the literature study method to explore and analyze data from various sources, including journal articles, books and theses. The findings of this research indicate the need for reform of family law in Islam to support gender equality and family welfare in an evolving social context.